2011
DOI: 10.1155/2011/960137
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rituximab in Autoimmune Hemolytic Anemia Associated with Non-Hodgkin Lymphomas

Abstract: The association between non-Hodgkin lymphomas and autoimmune disorders is a well-known event. Also autoimmune hemolytic anemia (AHA), although much more frequent in patients with chronic lymphocytic leukemia (CLL), has been described in this group of patients. In recent years, among the more traditional therapeutic options, rituximab, an anti-CD20 monoclonal antibody, has shown interesting results in the treatment of primary AHA. Although this drug has been frequently used for AHA in patients with CLL, much le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…A recent review approaching the paper of rituximab on the treatment on AIHA secondary to non-Hodgkin lymphoma concluded that it represents a valid therapeutic option, although a significant proportion of patients will relapse after an initial response. 8 The treatment's choice for our patient was based on staff experience and availability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review approaching the paper of rituximab on the treatment on AIHA secondary to non-Hodgkin lymphoma concluded that it represents a valid therapeutic option, although a significant proportion of patients will relapse after an initial response. 8 The treatment's choice for our patient was based on staff experience and availability.…”
Section: Discussionmentioning
confidence: 99%
“…In Sjogren's Syndrome, there is a 44 times increased risk of developing lymphoma. The presence of AIHA increases the risk of NHL by 2.6 fold [25]. Out of 175 patients on follow up for AIHA, a malignancy was found in 14% of them [8].…”
Section: Introductionmentioning
confidence: 99%
“…Аутоиммунная гСмолитичСская Π°Π½Π΅-мия (ΠΠ˜Π“Π) ослоТняСт Ρ‚Π΅Ρ‡Π΅Π½ΠΈΠ΅ ΠΎΡ‚ 3 Π΄ΠΎ 6% Π½Π΅Ρ…ΠΎΠ΄-Ткинских Π»ΠΈΠΌΡ„ΠΎΠΌ [13]. Π’ Ρ‚ΠΎ ΠΆΠ΅ врСмя Π’-ΠΊΠ»Π΅Ρ‚ΠΎΡ‡Π½Ρ‹Π΅ Π»ΠΈΠΌΡ„ΠΎΠΌΡ‹ Π² 39% случаСв ΡΠ²Π»ΡΡŽΡ‚ΡΡ ΠΏΡ€ΠΈΡ‡ΠΈΠ½ΠΎΠΉ Π²Ρ‚ΠΎ-Ρ€ΠΈΡ‡Π½ΠΎΠΉ ΠΠ˜Π“Π [19].…”
unclassified
“…Π’ нашСм случаС Π±Ρ‹Π»ΠΈ выявлС-Π½Ρ‹ ΠΊΠ°ΠΊ ΠΈΠ·ΠΎΠ»ΠΈΡ€ΠΎΠ²Π°Π½Π½ΠΎ Π‘3, Ρ‚Π°ΠΊ ΠΈ Ρ…ΠΎΠ»ΠΎΠ΄ΠΎΠ²Ρ‹Π΅ Π°Π³Π³Π»ΡŽΡ‚ΠΈ-Π½ΠΈΠ½Ρ‹ ΠΈ Π³Π΅ΠΌΠΎΠ»ΠΈΠ·ΠΈΠ½Ρ‹, Π° Ρ‚Π°ΠΊΠΆΠ΅ комбинация IgG/C3, которая ΡƒΠΊΠ°Π·Ρ‹Π²Π°Π΅Ρ‚ Π½Π° Π½Π°Π»ΠΈΡ‡ΠΈΠ΅ ΠΎΠ΄Π½ΠΎΠ²Ρ€Π΅ΠΌΠ΅Π½Π½ΠΎ Ρ‚Π΅ΠΏ-Π»ΠΎΠ²ΠΎΠΉ ΠΈ Ρ…ΠΎΠ»ΠΎΠ΄ΠΎΠ²ΠΎΠΉ Π°ΡƒΡ‚ΠΎΠΈΠΌΠΌΡƒΠ½Π½Ρ‹Ρ… Ρ€Π΅Π°ΠΊΡ†ΠΈΠΉ, Ρ‡Ρ‚ΠΎ, ΠΊΠΎΠ½Π΅Ρ‡Π½ΠΎ ΠΆΠ΅, усугубляСт Π°ΡƒΡ‚ΠΎΠΈΠΌΠΌΡƒΠ½Π½Ρ‹ΠΉ процСсс. ΠΠ˜Π“Π, обусловлСнная Ρ…ΠΎΠ»ΠΎΠ΄ΠΎΠ²Ρ‹ΠΌΠΈ антиэритроци-Ρ‚Π°Ρ€Π½Ρ‹ΠΌΠΈ Π°Π½Ρ‚ΠΈΡ‚Π΅Π»Π°ΠΌΠΈ, Ρƒ Π±ΠΎΠ»ΡŒΠ½Ρ‹Ρ… нСходТкинскими Π»ΠΈΠΌΡ„ΠΎΠΌΠ°ΠΌΠΈ ΠΏΡ€ΠΎΡ‚Π΅ΠΊΠ°Π΅Ρ‚ особСнно злокачСствСнно ΠΈ Ρ…ΡƒΠΆΠ΅ поддаСтся Π»Π΅Ρ‡Π΅Π½ΠΈΡŽ [13,16,18]. К Ρ‚ΠΎΠΌΡƒ ΠΆΠ΅, Ρ…ΠΎΠ»ΠΎΠ΄ΠΎΠ²Ρ‹Π΅ Π°Π³Π³Π»ΡŽΡ‚ΠΈΠ½ΠΈΠ½Ρ‹ (ΠΊΠΎΡ‚ΠΎΡ€Ρ‹Π΅ прСимущСствСн-Π½ΠΎ относятся ΠΊ IgM [21]) Π²ΡΡ‚Ρ€Π΅Ρ‡Π°Π»ΠΈΡΡŒ Ρ‚ΠΎΠ»ΡŒΠΊΠΎ Ρƒ ΠΏΠ°-Ρ†ΠΈΠ΅Π½Ρ‚ΠΎΠ² Π³Ρ€ΡƒΠΏΠΏΡ‹ II.…”
unclassified